Diagnóstico del clima organizacional en la escuela de educación básica Graciela Atarihuana de Cueva de la ciudad de Loja período 2022. - Rivera Robles, Cristian Xavier (2024)
The objective of this research work is to carry out a diagnosis of the organizational climate in the basic education school Graciela Atarihuana de Cueva in the city of Loja for the period 2022. For this purpose, there was a study population of 19 public servers where surveys were applied to 18 teachers and an interview only to the director of the institution. In order to carry out the Organizational Climate Diagnosis, it was necessary to address specific aspects such as determining the level of organizational climate and identifying the factors that positively and negatively influence the organizational climate of the basic education school Graciela Atarihuana de Cueva. Within the methodology for the completion of the following work we used the deductive, synthetic and analytical method with a mixed qualitative and quantitative approach that helped me to determine the results of the surveys and interview, which was done through the application of the questionnaire of the researcher Rensis Likert (1967) together with the Likert scale for the assessment of results obtained and for the interpretation of these results the adaptation of the Technical Standard for Measurement of Work Climate of the Public Service of the Ministry of Labor (2018) was performed. Thus, after the diagnosis it was determined that the organizational climate of the institution is at an average of 3.06 excellent, i.e., the perception of the work climate is well above average, which means that it is an important institutional strength for the achievement of the objectives of the entity.